History of the Second World War: Countering Attempts to Falsify and Distort to the Detriment of International Security - V. G. Kiknadze (Vestnik MGIMO-Universiteta)
One of the negative phenomena of the modern world are attempts to falsify history and the results of the Second World War, 1939-1945., is an important component of the ideological confrontation in the information space of neoliberal forces of Russian society with patriotic and non-violent, is a tool for achieving geopolitical goals of a number of states. United States, European Union and Ukraine tend to distort the results of the Second World War to remove the history of the Great Patriotic War, the feat of the Soviet people, who saved the world from fascism, and the Soviet Union (Russian Federation), together with Nazi Germany put in the dock of history, accusing all the troubles of the XX century. At the same time attempts to rehabilitate fascism and substitution postwar realities lead to the destruction of the entire system of contemporary international relations and, as a consequence, to the intensification of the struggle for the redivision of the world, including military measures. China is actively implementing the historiography of the statement that World War II began June 7, 1937 and is linked to an open aggression of Japan against China. Given these circumstances, the Military Doctrine of the Russian Federation noted that the trend of displacement of military dangers and military threats in the information space and the inner sphere of the Russian Federation. The main internal risks attributable activity information impact on the population, especially young citizens of the country, which has the aim of undermining the historical, spiritual and patriotic traditions in the field of defense of the Fatherland.